2013
DOI: 10.1109/tasc.2012.2233854
|View full text |Cite
|
Sign up to set email alerts
|

Development of High Strength Pancake Coil With Stress Controlling Structure by REBCO Coated Conductor

Abstract: High strength against electromagnetic force is required for high magnetic field and large capacity coil in order to develop large-capacity superconducting magnetic energy storage (SMES) systems for electric power system control. Also, suppression of delaminating of Yttrium (Y) based coated conductor in a coil is required to manufacture the highly reliable and durable superconducting coil. Insulating coating, using liquid resin of low-temperature-curable-polyamide, was developed and showed durability at very lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The hat structure may be similar to a Yoroi-coil structure, which has been proposed for reinforcement of the pancake coil wound by REBaCuO tape on the Hastelloy substrate, so that it may withstand the electromagnetic hoop stress [29,30]. The outer plates made of glass fibre reinforced plastics (GFRP) or carbon fibre reinforced plastics (CFRP) in the Yoroi-coil structure exist on the pancake coil.…”
Section: Overall Shrink-fit Effect From 540 K To 50 Kmentioning
confidence: 99%
“…The hat structure may be similar to a Yoroi-coil structure, which has been proposed for reinforcement of the pancake coil wound by REBaCuO tape on the Hastelloy substrate, so that it may withstand the electromagnetic hoop stress [29,30]. The outer plates made of glass fibre reinforced plastics (GFRP) or carbon fibre reinforced plastics (CFRP) in the Yoroi-coil structure exist on the pancake coil.…”
Section: Overall Shrink-fit Effect From 540 K To 50 Kmentioning
confidence: 99%
“…For magnets designs not requiring high spatial field homogeneity, other stress management designs are possible. For an SMES unit, Nagaya et al [113] are developing the 'Yoroi-coil' structure, where a part of the electromagnetic force is shifted from the conductor to the reinforcing outer plates situated at the side of the coil (figure 9). Using the Yoroi-coil structure concept, they demonstrated that it would be possible to push a calculated magnetic hoop stress of a 100 μm thick Hastelloy-backed conductor to beyond 1.6 GPa versus a typical conductor limit of 1.3 GPa [114].…”
Section: Coil Insulationmentioning
confidence: 99%
“…Fixed terminals with current leads cause the circumferentially nonuniform distribution of hoop stresses. The effects of metal reinforcement like over-band or YOROI structure [23] should be investigated in the near future.…”
Section: Discussionmentioning
confidence: 99%